A cof / au / aao nanofluidic hybrid membrane and a preparation method and application thereof

CN118142360BActive Publication Date: 2026-10-16NANJING NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410252326.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-06
Publication Date
2026-10-16
Estimated Expiration
2044-03-06

AI Technical Summary

Technical Problem

但目前用于光热离子选择性膜主要是对单一波长吸收性好,对丰富易得的太阳光利用率较低

Benefits of technology

[0024] The application of the COF/Au/AAO nanofluid hybrid membrane described in this invention in salinity gradient energy harvesting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118142360B_ABST
    Figure CN118142360B_ABST
Patent Text Reader

Abstract

The application discloses a COF / Au / AAO nanofluid hybrid membrane and a preparation method and application thereof, the hybrid membrane comprises a sulfonic acid COF and Au / AAO, the COF is in-situ grown on the Au / AAO, then a sulfonic acid group is modified in the COF hole, and the COF is connected with the Au / AAO through an Au-S bond; the preparation method is as follows: the Au / AAO with an asymmetric plasma structure is immersed into a beta-mercaptoethylamine solution, so that the mercapto in the beta-mercaptoethylamine is complexed with Au; then the Au / AAO is immersed into a solution containing 1,3,5-tri(4-aminophenyl)benzene and 1,4-dialdehyde-2,5-divinylbenzene precursors, dehydration condensation reaction is carried out, and finally, through a click reaction, 3-mercapto-1-propane sodium sulfonate is modified in the COF hole. The nanofluid hybrid membrane combines the Au / AAO with the sulfonic acid COF, can effectively utilize solar energy to generate a temperature gradient, promotes interface transmission, and significantly improves energy conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an ion channel composite membrane, and more particularly to a COF / Au / AAO nanofluid hybrid membrane, its preparation method, and its application. Background Technology

[0002] Energy crises and environmental pollution have become widespread problems, making the development of renewable, sustainable, and clean energy sources to replace traditional fossil fuels of great significance. Due to abundant marine resources, salinity gradient energy has emerged as a promising new energy source. This clean energy is typically obtained through reverse electrodialysis. However, the ion concentration polarization phenomenon prevalent during energy harvesting reduces the driving force for preferential ion transmembrane transport, leading to decreased mass transfer performance (ion permeability) and reduced output power of salinity gradient energy. Therefore, developing novel permeability-selective membranes that can effectively suppress concentration polarization while possessing both high ion selectivity and permeability is crucial for promoting salinity gradient energy harvesting.

[0003] Nanofluidic composite membranes, typically composed of two hybrid porous membranes, have attracted significant attention due to their asymmetric structure and ion-diode properties. The ion-diode effect of asymmetric membranes can promote unidirectional ion diffusion and block reverse current during energy conversion, thus significantly reducing Gibbs free energy dissipation caused by ion reflux. Currently, metal-organic frameworks (MOFs) and mesoporous silica (MCS) have been combined with anodic alumina (AAO) to construct nanofluidic devices, which exhibit unique ion rectification characteristics thanks to their asymmetric charge, composition, and structure. However, due to the high transport resistance at the hybrid membrane interface, the reported systems typically exhibit relatively low output power densities. Temperature control is an effective method to improve ion permeability and alleviate concentration polarization to enhance permeation power density. However, current research on temperature control usually involves heating the electrolytic cell solution, wasting considerable energy and diminishing the practical application prospects of permeation energy conversion. To address this challenge, many photothermal materials have been used to prepare ion exchange membranes, utilizing renewable solar energy storage. For example, Kong et al. (2022) used light-induced temperature gradients to drive ion migration in channels, thereby enhancing salinity gradient power generation performance. Wen et al. (2020) demonstrated a novel nanofluidic modulation strategy based on photo-induced thermally driven ion transport through layered MXene membranes. Applying light to off-center locations creates temperature gradients, which in turn drive ion transport, doubling the permeation energy conversion power density. However, current photothermal ion-selective membranes mainly exhibit good absorption of a single wavelength, resulting in low utilization of abundant and readily available sunlight.

[0004] Given the limited application of photothermal ion-selective membranes with full-band light absorption in salinity gradient energy harvesting, it is of great significance to develop heterogeneous membranes with high-efficiency photothermal conversion to promote interfacial transport, weaken concentration polarization, and thus enhance salinity gradient power generation. Summary of the Invention

[0005] Objectives of the Invention: The first objective of this invention is to provide a COF / Au / AAO nanofluid hybrid membrane with high efficiency in photothermal conversion to promote interfacial transport, reduce concentration polarization, and thus enhance salinity gradient power generation; the second objective of this invention is to provide a method for preparing the COF / Au / AAO nanofluid hybrid membrane; the third objective of this invention is to provide the application of the COF / Au / AAO nanofluid hybrid membrane in salinity gradient energy harvesting.

[0006] Technical solution: The COF / Au / AAO nanofluidic hybrid membrane of the present invention comprises sulfonic acid COF and Au / AAO. The COF is grown in situ on the surface of Au / AAO, and sulfonic acid groups are modified after a click reaction. The sulfonic acid COF and Au / AAO are connected through Au-S bonds; wherein the structural formula of the sulfonic acid COF is:

[0007]

[0008] Preferably, the thickness of the sulfonic acid COF is 0.2–0.5 micrometers. If the thickness is too low, the Au / AAO surface cannot be completely covered by the COF, resulting in lower output power; while if the thickness is too high, the ion transport resistance is high, limiting the output power.

[0009] Preferably, the pore size of the Au / AAO is 50–100 nm.

[0010] The method for preparing the COF / Au / AAO nanofluid hybrid membrane of the present invention includes the following steps:

[0011] (1) Au / AAO with an asymmetric plasma structure was prepared by magnetron sputtering from AAO prepared by anodic oxidation.

[0012] (2) Immerse Au / AAO in a β-mercaptoethylamine solution to allow the thiol groups in the β-mercaptoethylamine to complex with Au, then wash and dry;

[0013] (3) The Au / AAO treated in step (2) was immersed in a precursor solution containing 1,3,5-tris(4-aminophenyl)benzene (Tab) and 1,4-dialdehyde-2,5-divinylbenzene (Dva) to undergo a dehydration condensation reaction to obtain an unmodified COF / Au / AAO nanofluid hybrid membrane.

[0014] (4) The unmodified COF / Au / AAO membrane after step (3) is immersed in an aqueous solution made of deionized water, sodium 3-mercapto-1-propanesulfonate (3MPS) and 2,2'-azobis(2-methylpropylamidine) dihydrochloride (AAPH). The solution is purged with nitrogen and reacted at 70-80°C under a nitrogen atmosphere to modify the COF pores with sulfonic acid groups, thus obtaining a sulfonic acid-modified COF / Au / AAO nanofluid hybrid membrane.

[0015] In step (2), the thiol group in β-mercaptoethylamine complexes with Au, and in subsequent reactions, COF is connected to Au / AAO via Au-S bonds.

[0016] Preferably, in step (2), the concentration of the β-mercaptoethylamine solution is 1 to 10 mM.

[0017] In step (3), 1,3,5-tris(4-aminophenyl)benzene and 1,4-dialdehyde-2,5-divinylbenzene undergo a dehydration condensation reaction to grow COF in situ on the Au / AAO surface.

[0018] Preferably, in step (3), the molar ratio of 1,3,5-tris(4-aminophenyl)benzene to 1,4-dialdehyde-2,5-divinylbenzene is 1:1 to 2; and the concentration of 1,4-dialdehyde-2,5-divinylbenzene is 15 to 20 mM.

[0019] Preferably, in step (3), the precursor solution is a mixture of o-dichlorobenzene and n-butanol as solvents. More preferably, o-dichlorobenzene and n-butanol are mixed at a volume ratio of 1:1.

[0020] Preferably, in step (3), the dehydration condensation reaction temperature is 100-120°C.

[0021] In step (4), sulfonic acid groups are modified into COF pores by click reaction.

[0022] Preferably, in step (4), the concentration of sodium 3-mercapto-1-propanesulfonate is 40-80 mM.

[0023] Preferably, in step (4), the reaction time is 24 to 48 hours.

[0024] The application of the COF / Au / AAO nanofluid hybrid membrane described in this invention in salinity gradient energy harvesting.

[0025] Mechanism of Invention: This invention constructs a COF / Au / AAO nanofluidic hybrid membrane by combining an ultra-high pore density sulfonic acid covalent organic framework (COF) with Au / AAO. The COF layer modified with sulfonic acid groups possesses ordered and high-density pores, ensuring abundant permeability. Due to the large number of sulfonic acid groups in its structure, the COF exhibits excellent cation selectivity. The Au / AAO membrane provides strong support and can effectively utilize solar thermal energy to generate a temperature gradient, promoting interfacial transport. The prepared COF / Au / AAO nanofluidic hybrid membrane can generate a temperature gradient exceeding 50°C under illumination, significantly improving permeability while maintaining ion selectivity, and weakening concentration polarization, thereby significantly improving energy conversion efficiency.

[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The nanofluid hybrid membrane, by combining Au / AAO with sulfonic acid COF, can effectively convert solar energy into thermal energy to generate a temperature gradient, promote interfacial transport, and significantly improve energy conversion efficiency; (2) With a sulfonic acid COF thickness of 200 nm, the output power density of the hybrid membrane is 9.3 W / m under a 50-fold salt concentration gradient. 2 After illumination, it increased to 15.7 W / m 2 (3) The nanofluid hybrid membrane has good stability; (4) The preparation method is simple and easy to industrialize. Attached Figure Description

[0027] Figure 1 The flowchart illustrates the preparation process of the COF / Au / AAO nanofluid hybrid membrane for this invention.

[0028] Figure 2 A scanning electron microscope image of the COF / Au / AAO nanofluid hybrid film prepared in Example 1;

[0029] Figure 3 The infrared spectrum of the COF / Au / AAO nanofluid hybrid film prepared in Example 1;

[0030] Figure 4 The XPS photoelectron spectrum of the COF / Au / AAO nanofluid hybrid film prepared in Example 1;

[0031] Figure 5 The N2 adsorption / desorption isotherm spectrum of the COF / Au / AAO nanofluid hybrid membrane prepared in Example 1;

[0032] Figure 6 The graph shows the effect of salt concentration on ion rectification.

[0033] Figure 7 This is a graph showing the effect of pH on ion rectification.

[0034] Figure 8The photoresponse current diagram is shown for the COF / Au / AAO nanofluid hybrid film prepared in Example 1.

[0035] Figure 9 Power density plots of COF / Au / AAO nanofluid hybrid films with different COF thicknesses;

[0036] Figure 10 Power density diagrams of the COF / Au / AAO nanofluid hybrid membrane prepared in Example 1 under different salt concentration gradients;

[0037] Figure 11 Power density diagram of the COF / Au / AAO nanofluid hybrid film prepared in Example 1 under different light irradiation powers;

[0038] Figure 12 Power density diagram of the COF / Au / AAO nanofluid hybrid film prepared in Example 1 at different working areas;

[0039] Figure 13 Stability power density diagram of the COF / Au / AAO nanofluid hybrid membrane prepared in Example 1 after being placed for different number of days. Detailed Implementation

[0040] The technical solution of the present invention will be further described below with reference to the embodiments.

[0041] Example 1

[0042] like Figure 1 As shown, the method for preparing the COF / Au / AAO nanofluid hybrid film of the present invention includes the following steps:

[0043] (1) Place the AAO in the chamber of a magnetron sputtering instrument of model GMC-1000, and set the vacuum degree, sputtering current and sputtering time to 5 Pa, 10-30 mA and 240-480 s, respectively, to prepare Au / AAO with an asymmetric plasma structure.

[0044] (2) The Au / AAO asymmetric plasma structure was functionalized by immersing it in a 10 mM β-mercaptoethylamine aqueous solution for 3 hours, then washed with water and vacuum dried.

[0045] (3) Dissolve 14.06 mg of 1,3,5-tris(4-aminophenyl)benzene (10 mmol / L) and 11.17 mg of 1,4-dialdehyde-2,5-divinylbenzene (15 mmol / L) in a mixed solution of 2 mL of o-dichlorobenzene, 2 mL of n-butanol and 0.2 mL of 6 mol / L acetic acid. Then, sonicate the reaction solution for 10 minutes to obtain a homogeneous COF precursor solution.

[0046] (4) Place the β-mercaptoethylamine modified Au / AAO membrane at the bottom of the reaction vessel, add the COF precursor solution, and react at 100°C for 72 hours. After the reaction is completed, wash the unmodified COF / Au / AAO composite membrane with acetone and detetrahydrofuran respectively and then vacuum dry.

[0047] (5) The unmodified COF / Au / AAO membrane was immersed in an aqueous solution prepared by deionized water and sodium 3-mercapto-1-propanesulfonate (80 mmol / L) and 2,2'-azobis(2-methylpropylamidine) dihydrochloride (5 mmol / L). Before heating, the solution was purged with nitrogen at room temperature for 30 min and reacted at 70 °C for 24 h under a nitrogen atmosphere. After the reaction, the COF / Au / AAO composite membrane was washed with deionized water and dried under vacuum.

[0048] The COF / Au / AAO composite film obtained has a COF thickness of 200 nm.

[0049] Example 2

[0050] Based on Example 1, the reaction time in step (4) was changed to 96 hours.

[0051] The COF / Au / AAO composite membrane obtained has a COF sulfonic acid thickness of 2 μm.

[0052] Example 3

[0053] Based on Example 1, in step (4), the reaction temperature is 90°C, the reaction time is 72 hours, and the other conditions remain unchanged.

[0054] The COF / Au / AAO composite membrane obtained has a sulfonic acid COF thickness of 100 nm.

[0055] Example 4

[0056] Based on Example 1, in step (4), the reaction temperature is 120°C, the reaction time is 72 hours, and the other conditions remain unchanged.

[0057] The COF / Au / AAO composite membrane obtained has a sulfonic acid COF thickness of 500 nm.

[0058] Comparative Example 1

[0059] Based on Example 1, the reaction time in step (3) was changed to 48 hours.

[0060] The COF / Au / AAO composite membrane obtained has a sulfonic acid COF thickness of 50 nm.

[0061] Comparative Example 2

[0062] Based on Example 1, the reaction time in step (3) was changed to 24 hours.

[0063] The COF / Au / AAO composite membrane obtained has a sulfonic acid COF thickness of 20 nm.

[0064] Structural characterization

[0065] The COF / Au / AAO nanofluid hybrid film structure prepared in Example 1 was characterized, and the results are as follows: Figures 2-5 .

[0066] Depend on Figure 2 Scanning electron microscopy images show that gold of varying asymmetric sizes is attached to the channels of AAO with a pore size of approximately 70 nm, and a layer of sulfonic acid COF with a thickness of approximately 200 nm is grown in situ on the surface of Au / AAO.

[0067] Depend on Figure 3 The infrared spectrum shows that at 1610 cm⁻¹ -1 A new absorption peak appears at 1040 cm⁻¹, which is assigned to the C=N tensile vibration. Furthermore, at 1040 cm⁻¹... -1 and 669cm -1 Characteristic peaks were observed at [location], which correspond to O=S=O and CS asymmetric stretching, respectively. This confirms the successful modification of the sulfonate group within the COF framework.

[0068] Depend on Figure 4 The X-ray photoelectron spectroscopy confirmed the presence of an S2p signal on the COF / Au / AAO surface, indicating the successful composite of the COF / Au / AAO nanoheterofilm.

[0069] Figure 5 The figure shows the N2 adsorption / desorption isotherm spectrum of COF in the COF / Au / AAO nanofluidic hybrid film prepared in Example 1. As can be seen from the figure, COF forms uniformly distributed sub-2nm channels, with most pores having a size of approximately 1.78nm and a diameter of 150.9m. 2 g –1 The high specific surface area further demonstrates the excellent porous structure of COF.

[0070] Performance testing

[0071] 1. Rectification characteristics of COF / Au / AAO nanofluid hybrid films

[0072] The rectification characteristics of the COF / Au / AAO nanofluid hybrid membrane prepared in Example 1 were tested.

[0073] (1) Effect of salt concentration on ion rectification

[0074] Test method: KCl solutions of different concentrations were filled into the electrolytic cell, and the IV curve was detected using an electrochemical workstation. The results are as follows. Figure 6 As shown.

[0075] like Figure 6 As shown, by changing the solution concentration (0.01 mM to 1 M), it can be observed that the ion current increases with increasing ion concentration; the ion rectification ratio reaches its maximum value at 10 mM and then decreases with further increases in solution concentration. This further proves that ion transport is controlled by the electric double layer, and the ion rectification effect is most significant when the double layer thickness is at its maximum.

[0076] (2) Effect of pH on ion rectification

[0077] Test method: KCl solutions with different pH values ​​were filled into the electrolytic cell, and the IV curve was detected using an electrochemical workstation. The test results are as follows: Figure 7 As shown.

[0078] Depend on Figure 7 It can be seen that as the pH value changes from 11.0 to 4.0, the ion rectification ratio gradually decreases, and then becomes less than 1 at pH 3.0. Correspondingly, as the pH value changes from 11.0 to 4.0, the Zeta potential decreases from -44.2 mV to -10.4 mV, and at pH 3.0, the Zeta potential remains at 3.5 mV as expected. This indicates that the device exhibits good acid and alkali resistance over a wide range.

[0079] 2. Application of COF / Au / AAO nanofluidic hybrid membrane in salinity gradient energy harvesting

[0080] When the COF / Au / AAO nanofluidic hybrid membrane is installed in the electrolytic cell, the small-hole end of the gasket faces the COF side and a high-concentration solution is placed in the cell, while the large-hole end of the gasket faces the AAO side and a low-concentration solution is placed in the cell. Light shines from the AAO side to the COF side. The entire energy harvesting device consists of an Ag / AgCl electrode, a load resistor, wires, a xenon lamp, and an electrolytic cell (containing the COF / Au / AAO composite membrane and salt solutions of different concentrations).

[0081] (1) Response of COF / Au / AAO composite film to light

[0082] The COF / Au / AAO nanofluid hybrid membrane prepared in Example 1 was used in a NaCl solution with a 50-fold salinity gradient (10 mM / 0.5 M). The short-circuit current change over time was tested under no-light conditions. The test results are as follows: Figure 8 As shown.

[0083] Depend on Figure 8It can be seen that the current value changes with the light switch. When the light is on, the current rapidly increases to its maximum value and then tends to stabilize; when the light is off, the current rapidly decreases and remains stable, showing good cycle stability.

[0084] (2) The effect of different COF thickness in COF / Au / AAO nanofluidic hybrid membrane on salinity gradient energy harvesting

[0085] Examples 1-2 and Comparative Examples 1-2 were conducted by controlling the COF monomer reaction time to 72 hours, 96 hours, 48 ​​hours, and 24 hours. The thicknesses of Examples 1 and 2 were 200 nm and 2 μm, respectively, while Comparative Examples 1 and 2 did not completely cover the Au / AAO substrate. External circuit power (10 mM / 0.5 M) was tested at a 50-fold salt gradient, and the results are as follows... Figure 9 As shown.

[0086] Depend on Figure 9 It was found that the external circuit power densities of the COF / Au / AAO nanofluid hybrid films prepared in Examples 1-2 and Comparative Examples 1-2 were 9.30 W / m², respectively. 2 5.47W / m 2 3.84W / m 2 and 2.19W / m 2 When the COF thickness is in the range of 0.2–1.0 μm, the substrate is not only completely covered, but also exhibits low ion transport resistance, thus demonstrating excellent output power density. If the COF thickness is too low, it cannot completely cover the AAO substrate, resulting in low output power. If the COF material is too thick, the ion transport resistance is high, leading to low output power.

[0087] (3) Harvesting salinity gradient energy using composite membranes under different salinity gradients

[0088] Using the COF / Au / AAO nanofluid hybrid membrane prepared in Example 1, the AAO side solution concentration was controlled at 10 mM. By changing the COF side solution concentration from 0.5 M to 5 M, the external circuit current density and power density were tested, and the results are as follows. Figure 10 As shown.

[0089] Depend on Figure 10 It can be seen that both current density and power density increase with increasing salinity gradient, and the output power density reaches as high as 43.22 W / m² at a salinity gradient of 500 times. 2 .

[0090] (4) Collection of salinity gradient energy using composite membranes under different light irradiances

[0091] Using the COF / Au / AAO nanofluid hybrid membrane prepared in Example 1, the salinity gradient was fixed at 50 times, and the light irradiation power was adjusted to 0 mW / cm². 2 50mW / cm 2 100mW / cm 2 and 200mW / cm 2 The power density of the external circuit was tested, and the results are as follows: Figure 11 As shown.

[0092] Depend on Figure 11 Therefore, when the light power is 0mW / cm 2 50mW / cm 2 100mW / cm 2 and 200mW / cm 2 At that time, the corresponding external circuit power density was 9.3 W / m. 2 11.8W / m 2 13.6W / m 2 and 15.7W / m 2 This indicates that as the optical power increases, the output power also increases.

[0093] (5) Collection of salinity gradient energy using composite membranes with different pore areas

[0094] Using the COF / Au / AAO nanofluid hybrid membrane prepared in Example 1, with the salinity gradient fixed at 50 times, the working area for testing salinity gradient power generation can be changed by altering the pore size of the PDMS gasket sandwiched between the two electrolyzers. The testing area was adjusted to 0.03 mm. 2 0.1256mm 2 0.785mm 2 and 3.14mm 2 The power density of the external circuit was tested, and the results are as follows: Figure 12 As shown.

[0095] Depend on Figure 12 Therefore, the test area was adjusted to 0.03 mm. 2 0.1256mm 2 0.785mm 2 and 3.14mm 2 At that time, the corresponding external circuit power density was 9.30 W / m. 2 3.43W / m 2 0.96W / m 2 and 0.24W / m 2 This indicates that high output power can only be achieved in a small operating area, mainly due to the phenomenon of concentration polarization.

[0096] (6) Stability of composite membrane during salinity gradient energy harvesting

[0097] The COF / Au / AAO nanofluidic hybrid membrane prepared in Example 1 was continuously immersed in water for 10 days. The output power density of the external circuit was tested at 0, 1, 3, 5, and 10 days of immersion. The results are as follows. Figure 13 As shown.

[0098] Depend on Figure 13 It can be seen that the COF / Au / AAO nanofluid hybrid membrane still has a stable output power density after being immersed for 10 days.

Claims

1. A method for preparing a COF / Au / AAO nanofluid hybrid membrane, characterized in that, Includes the following steps: (1) Au / AAO with an asymmetric plasma structure was prepared by magnetron sputtering from AAO prepared by anodic oxidation. (2) Immerse Au / AAO in a β-mercaptoethylamine solution to allow the thiol groups in the β-mercaptoethylamine to complex with Au, then wash and dry; (3) The Au / AAO treated in step (2) was immersed in a solution containing 1,3,5-tris(4-aminophenyl)benzene and 1,4-dialdehyde-2,5-divinylbenzene precursors and dehydrated and condensed to obtain an unmodified COF / Au / AAO nanofluid hybrid membrane. (4) The unmodified COF / Au / AAO membrane after step (3) is immersed in an aqueous solution made of deionized water, sodium 3-mercapto-1-propanesulfonate and 2,2'-azobis(2-methylpropylamidine) dihydrochloride. The solution is purged with nitrogen and reacted at 70~80°C under a nitrogen atmosphere to modify the COF pores with sulfonic acid groups, thus obtaining a sulfonic acid-modified COF / Au / AAO nanofluid hybrid membrane. In step (2), the concentration of the β-mercaptoethylamine solution is 1~10 mM; In step (3), the molar ratio of 1,3,5-tris(4-aminophenyl)benzene to 1,4-dialdehyde-2,5-divinylbenzene is 1:1.5~2; In step (4), the concentration of sodium 3-mercapto-1-propanesulfonate is 40~80 mM.

2. The method for preparing the COF / Au / AAO nanofluid hybrid membrane according to claim 1, characterized in that, In step (3), the dehydration condensation reaction temperature is 90 ~ 120 ℃.

3. The method for preparing the COF / Au / AAO nanofluid hybrid membrane according to claim 1, characterized in that, In step (3), the solvent of the precursor solution is a mixture of o-dichlorobenzene and n-butanol.

4. A COF / Au / AAO nanofluid hybrid membrane prepared by the preparation method according to any one of claims 1 to 3, characterized in that, This includes sulfonic acid COF and Au / AAO. The COF is grown in situ on the Au / AAO surface and modified with sulfonic acid groups using a click reaction. The sulfonic acid COF is linked to Au / AAO via Au-S bonds. The structural formula of the sulfonic acid COF is as follows: 。 5. The COF / Au / AAO nanofluid hybrid membrane according to claim 4, characterized in that, The thickness of the COF is 0.2 to 2 micrometers.

6. The COF / Au / AAO nanofluid hybrid membrane according to claim 4, characterized in that, The pore size of the Au / AAO is 50~100 nm.

7. The application of the COF / Au / AAO nanofluidic hybrid membrane according to any one of claims 4 to 6 in salinity gradient energy harvesting.